Mocarstwo słabych – o wartości starców w kulturze ludowej - Kalniuk, Tomasz (Wydawnictwo Naukowe UAM, 2013)
The folk culture from the turn of the 20 th century was founded on the mythical paradigm. Its specific feature was an opposition between the selfand the other. It had ambivalent influence on those people and places which, due to actual or perceptual reasons, were placed on the margin of the mainstream of life. This includes, among others, the elders. On the one hand, they were treated by the community with reluctance, or even aggression, because of their decrepitude. On the other hand, they were respectedas guards of traditions, and intermediaries with the supernatural, who possessed a portion of its potential.
The Power of the Weak: on Worthiness of Elders in Folk Culture
Keywords: borders; elders; folk culture; myth; old age; others; sacrum; supernatural